2014
DOI: 10.1111/acer.12445
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double-Blind, Placebo-Controlled Trial of Quetiapine in Patients with Bipolar Disorder, Mixed or Depressed Phase, and Alcohol Dependence

Abstract: Background Alcohol dependence is common in bipolar disorder (BPD) and associated with treatment non-adherence, violence, and hospitalization. Quetiapine is a standard treatment for BPD. We previously reported improvement in depressive symptoms, but not alcohol use, with quetiapine in BPD and alcohol dependence. However, mean alcohol use was low and a larger effect size on alcohol-related measures was observed in those with higher levels of alcohol consumption. In this study, efficacy of quetiapine in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 34 publications
(49 reference statements)
0
24
1
Order By: Relevance
“…Only eight articles, including seven unique studies (including post-hoc of overlapping samples) were identified that met our inclusion criteria. Six out of the seven included results were double-blind, placebo-controlled trials [ 14 , 29 , 30 , 31 , 32 , 33 , 34 ]. Overall, the methodological quality of the randomized controlled studies was good, scoring ≥3 according to the Jadad scale [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only eight articles, including seven unique studies (including post-hoc of overlapping samples) were identified that met our inclusion criteria. Six out of the seven included results were double-blind, placebo-controlled trials [ 14 , 29 , 30 , 31 , 32 , 33 , 34 ]. Overall, the methodological quality of the randomized controlled studies was good, scoring ≥3 according to the Jadad scale [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…Aripiprazole as monotherapy or augmentation treatment was also documented to be superior over placebo in terms of efficacy, though no clear-cut quantitative measure was provided about this outcome [ 39 ]. On the contrary, quetiapine did not reduce alcohol consumption in patients with either BD and/or depressive mixed phase and alcohol consumption when compared against placebo [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our data are consistent with a recently published study, investigating efficacy of Quetiapine in treating alcohol dependence in patients diagnosed with bipolar disorder. The authors found that although Quetiapine treatment did not yield anticipated lowering of alcohol intake, patients experienced an increase in akathisia symptoms at 6 weeks (BARS score, p = 0.04), but not at 12 weeks [30]. At baseline, the likelihood of akathisia incidence in high MADRS group compared to low MADRS group was low.…”
Section: Resultsmentioning
confidence: 99%
“…Quetiapine add‐on therapy was not more effective than placebo add‐on in reducing the number of drinks per day or other alcohol‐related measures in patients with BDI699 or BDI and BDII with alcohol dependence (level 1 negative) 700. In another RCT, quetiapine monotherapy or add‐on therapy to mood stabilizers was compared with placebo monotherapy or add‐on therapy in patients with bipolar depression with comorbid anxiety and substance use disorders 701.…”
Section: Specific Populationsmentioning
confidence: 98%